2006
DOI: 10.1186/1476-069x-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to the fungicide vinclozolin causes virilization of females and alteration of progesterone receptor expression in vivo: an experimental study in mice

Abstract: BackgroundVinclozolin is a fungicide that has been reported to have anti-androgenic effects in rats. We have found that in utero exposure to natural or synthetic progesterones can induce hypospadias in mice, and that the synthetic progesterone medroxyprogesterone acetate (MPA) feminizes male and virilizes female genital tubercles. In the current work, we selected a relatively low dose of vinclozolin to examine its in utero effects on the development of the genital tubercle, both at the morphological and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
(21 reference statements)
0
32
0
Order By: Relevance
“…Nevertheless, early exposure to vinclozolin led to some female virilization, as shown by AGD at PND21, suggesting a predominantly androgenic effect, which was previously reported for the female reproductive tract (Buckley et al 2006). This apparent discrepancy could be the result of the androgen agonist activities of the M2 vinclozolin metabolites (Molina-Molina et al 2006;Wong et al 1995), since a complementary study indicated that M2 metabolite, but not vinclozolin, was recovered in the plasma and milk of lactating mothers (Auger et al 2010).…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, early exposure to vinclozolin led to some female virilization, as shown by AGD at PND21, suggesting a predominantly androgenic effect, which was previously reported for the female reproductive tract (Buckley et al 2006). This apparent discrepancy could be the result of the androgen agonist activities of the M2 vinclozolin metabolites (Molina-Molina et al 2006;Wong et al 1995), since a complementary study indicated that M2 metabolite, but not vinclozolin, was recovered in the plasma and milk of lactating mothers (Auger et al 2010).…”
Section: Discussionmentioning
confidence: 77%
“…Further analysis of the in utero effects of vinclozolin revealed that male embryos underwent feminization and female embryos became masculinized when dams were given vinclozolin. As suggested by the data, the morphogenic actions of vinclozolin within embryos could be a result of the effects of this compound on the expression of AR, ER, and/ or progesterone receptors [136].ii. DDE-Another compound possessing anti-androgen activity is the DDT metabolite 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (DDE) [137].…”
mentioning
confidence: 90%
“…Vinclozolin (VCZ), a fungicide possessing an anti-androgenic activity affected spermatogenesis inducing decreases in sperm number and motility and an increase in apoptosis in the seminiferous tubules germ cells (Shimamura et al 2002, Anway et al 2005, Buckley et al 2006, Elzeinova et al 2008. MXC, administered perinatally or during gestation, was also found to affect spermatogenesis in the adult or in the offspring respectively (Chapin et al 1997, Anway et al 2005).…”
Section: Introductionmentioning
confidence: 99%